Microbial, physicochemical and sensory characteristics analysis of selected alcoholic beverages of from Bangladesh, India and Nepal (Journal of Bio-Science, 2018)
Alcoholic beverage is a drink containing ethanol, commonly known as alcohol. Beer is the most widely used alcoholic beverage in the world. To analyze the microbial, physicochemical and sensory characteristics of selected alcoholic beverages, several selected alcoholic beverages (power, strong, crown, hunter, power horse, god father, thunder, bag piper, commando and star gold) of Bangladesh, India and Nepal were used in this study for their analysis. Microbial analysis, physiochemical analysis, and sensory analysis were performed by using standard methods. The results of microbial analysis showed that the standard plate counts of alcoholic beverages were less than 300 colonies. The fungi were present in Nepal and Bangladesh sample but not in Indian samples. In all samples, the presence of coliform was about 0.03/ ml to 2.4/ ml. In nutrient agar, creamy smooth colony was found in most of the Nepal and Bangladesh beverages but not in Indian beverages. Hunter contained the highest pH (4.6) whereas power and bag piper showed the lowest pH values (3.3), strong contained maximum total solid (19.2%) but bag piper had only 2% total solid, big piper contained the highest amount of alcohol (18.25%) although power contained only 3.15% alcohol. Sensory evaluation of all the samples was quite acceptable as an alcoholic beverage. Among the alcoholic beverages it might be concluded that Nepal beverages are the best product in respect of sensory evaluation, but considering microbial analysis Indian beverages are the best.J. bio-sci. 23: 67-75, 2015